2004
DOI: 10.1002/cncr.20434
|View full text |Cite
|
Sign up to set email alerts
|

Oncolysis by viral replication and inhibition of angiogenesis by a replication‐conditional herpes simplex virus that expresses mouse endostatin

Abstract: BACKGROUND In preclinical models, infection of tumors by oncolytic strains of herpes simplex virus 1 (HSV‐1) resulted in the destruction of tumor cells by viral replication and release of progeny virion that infected and destroyed adjacent tumor cells. However, complete tumor regression was rarely observed. METHODS To augment the antitumor effect of viral oncolysis, a replication conditional HSV‐1 mutant (HSV‐Endo) was constructed in which the murine endostatin gene was incorporated into the HSV‐1 genome. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Oncolytic HSV-1 vectors have been used successfully to deliver immunoregulatory molecules, prodrug converting enzymes and angiogenesis inhibitors. 212 Synergism of antitumor effect was observed when oncolytic HSV-1 mutants were engineered to express cytokines. An elegant experiment done by Andreansky et al 213 clearly demonstrated that cytokine expression may be an important adjunct to oncolytic HSV-1 therapy.…”
Section: Armed Oncolytic Virusmentioning
confidence: 99%
“…Oncolytic HSV-1 vectors have been used successfully to deliver immunoregulatory molecules, prodrug converting enzymes and angiogenesis inhibitors. 212 Synergism of antitumor effect was observed when oncolytic HSV-1 mutants were engineered to express cytokines. An elegant experiment done by Andreansky et al 213 clearly demonstrated that cytokine expression may be an important adjunct to oncolytic HSV-1 therapy.…”
Section: Armed Oncolytic Virusmentioning
confidence: 99%
“…[27][28][29] There are many attempts to engineer viruses to express antiangiogenic molecules. [30][31][32] Also obscuring the true effect of oncolytic herpes viruses on angiogenesis is the fact that all data have been generated in animal models rather than clinical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Viral therapeutics can be tailored to attack genetic defects commonly found in tumor cells (2). Several oncolytic viruses (either native or genetically engineered), such as replication-competent adenovirus (3), herpes simplex virus (HSV) (4), and vesicular stomatitis virus (VSV) (5) carrying foreign genes have been reported to behave like 'armed' virus vectors in cancer treatment. The use of replication-competent viral vectors instead of traditional replication-defective viruses allows amplification of the potential therapeutic anti-tumor effects (6,7).…”
Section: Introductionmentioning
confidence: 99%